2022
DOI: 10.1371/journal.pone.0264637
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer-specific mortality in early breast cancer as defined by high-risk clinical and pathologic characteristics

Abstract: Objectives To investigate breast cancer-specific mortality by early breast cancer (EBC; Stages I-IIIC) subtype; incidence of high-risk indicators for recurrence (defined in monarchE trial); and mortality risk difference by those who did/did not meet these criteria. Materials and methods Analyses included patients with initial EBC diagnosis between 2010–2015 from Surveillance, Epidemiology, and End Results (SEER) data (n = 342,149). Cox proportional hazards models and Kaplan-Meier estimates examined mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
1
18
1
8
Order By: Relevance
“…3 a). With the focus on HRpos/HER2neg patients, sorting patients according to the MonarchE study inclusion and exclusion criteria showed that the patients channeled into the study MonarchE study made up approximately 13 % of all the HRpos/HER2neg patients investigated in this analysis [26]. Moreover, it was shown that after 6 years, patients with triple negative disease had a similar prognosis to those who were eligible for the MonarchE study (▶ Fig.…”
Section: Prognosis and Medical Need In Adjuvant Hrpos/her2neg Patient...mentioning
confidence: 95%
See 2 more Smart Citations
“…3 a). With the focus on HRpos/HER2neg patients, sorting patients according to the MonarchE study inclusion and exclusion criteria showed that the patients channeled into the study MonarchE study made up approximately 13 % of all the HRpos/HER2neg patients investigated in this analysis [26]. Moreover, it was shown that after 6 years, patients with triple negative disease had a similar prognosis to those who were eligible for the MonarchE study (▶ Fig.…”
Section: Prognosis and Medical Need In Adjuvant Hrpos/her2neg Patient...mentioning
confidence: 95%
“…For example, the Mon- ▶ Fig. 3 a Breast cancer-specific survival according to groups defined by hormone receptor status and HER2 status (data from [26]). b Survival rates for TNBC patients and for HRpos/HER2neg patients who do and do not meet the inclusion criteria for the MonarchE study (data from [26]).…”
Section: Prognosis and Medical Need In Adjuvant Hrpos/her2neg Patient...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor grade (by assessment of histologic differentiation) and stage (TNM, Tumor size, Nodal status, and distant Metastasis) have also important prognostic roles and they are considered in a number of clinical decisions [ 2 ]. Early breast cancer accounts for > 90% of all diagnosed breast cancers and despite the availability of different treatment options, ~ 30% of these patients will develop cancer recurrence/progression [ 4 ]. Locally advanced or metastatic breast cancers have a median overall survival of approximately ∼3 years and the 5-year survival is only ∼25% [ 5 ].…”
Section: The Pleiotropic Role Of Gcs and Breast Cancermentioning
confidence: 99%
“…Breast cancer is categorized into subtypes according to tumor characteristics, including hormone receptor (HR) status and human epidermal growth factor receptor 2 (HER2) overexpression, which support treatment decisions [ 6 , 7 ]. About two-thirds of BCs are HR positive (HR+), 13%–20% are HER2 positive, and 12% are classified as triple-negative BC (TNBC) [ [8] , [9] , [10] ]. Another factor that impacts BC risk and treatment options is the presence of germline mutations in BC susceptibility gene 1 or 2 (g BRCA1/2 mut).…”
Section: Introductionmentioning
confidence: 99%